Nine Equivalents of Nursing Manpower Use Score (NEMS): um estudo de seu processo histórico Nine Equivalents of Nursing Manpower Use Score (NEMS): un estudio de su proceso histórico Nine Equivalents of Nursing Manpower Use Score (NEMS): a study of its historical process - Simone Travi Canabarro; Kelly Dayane Stochero Velozo; Olga Rosária Eidt; Jefferson Pedro Piva; Pedro Celiny Ramos Garcia (Universidade Federal do Rio Grande do Sul, 2010)
Este estudo visa, por meio de uma revisão integrativa da literatura, descrever o percurso histórico dos escores de intervenções terapêuticas com ênfase no Nine Equivalents of Nursing Manpower Use Score (NEMS) em Unidade de Terapia Intensiva. Foram utilizados os descritores "Unidades de terapia intensiva" e "escalas" para publicações entre 2000 e 2009. Foram selecionados "Nine Equivalents of Nursing Manpower Use Score" ou "NEMS", "Unidade de Terapia Intensiva", "Therapeutic Intervention Scoring System-76", "Therapeutic Intervention Scoring System-28 ou "TISS-28". Selecionaram-se publicações das bases Medical Literature Analysis and Retrieval System Online (MEDLINE) e Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS). Dos 295 artigos capturados, 18 foram incluídos, sendo 55,5% em inglês. Os estudos abordam o NEMS (33,3%), Therapeutic Intervention Scoring System-76 (11,1%), TISS-28 (33,3%), entre outros. Pesquisas destacaram que o NEMS vem demonstrando ser uma ferramenta útil, operacional e sucinta. Este estudio tiene el objetivo de, através de una revisión integradora de la literatura, describir el recorrido histórico de los puntajes de intervenciones terapéuticas con énfasis en el Nine Equivalents of Nursing Manpower Use Score (NEMS), en Unidades de Cuidados Intensivos. Se utilizaron los descriptores "Unidades de terapia intensiva" y escalas" para publicaciones entre 2000 y 2009. Han sido seleccionados "Nine Equivalents of Nursing Manpower Use Score" o "NEMS", "Unidade de Terapia Intensiva", "Therapeutic Intervention Scoring System-76", "Therapeutic Intervention Scoring System-28 o "TISS-28". Se seleccionaron publicaciones de las bases Medical Literature Analysis and Retrieval System Online (MEDLINE) y Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS). De los 295 artículos elegidos se incluyeron 18, entre los cuales 55,5% en inglés. Los estudios enfocaron el NEMS (33,3%), Therapeutic Intervention Scoring System-76 (11,1%), TISS-28 (33,3%), entre otros. Investigaciones han destacado que el NEMS ha demostrado ser una herramienta útil, operacional y sucinta. This study conducted a integrative review of the literature with the objective of describing the historical trajectory of therapeutic interventions scores with emphasis on Nine Equivalents of Nursing Manpower Use Score in Intensive Care Units. The descriptors used were "Intensive care units" and "scales", for publications issued between 2000 and 2009. The sensitized terms were: "Nine Equivalents of Nursing Manpower Use Score" or "NEMS", "Unidade de Terapia Intensiva", "Therapeutic Intervention Scoring System-76", "Therapeutic Intervention Scoring System-28 or "TISS-28". Medical Literature Analysis and Retrieval System Online (MEDLINE) and Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS) publications were selected. Among the 295 papers reviewed, 18 were chosen, of which 55,5% were in English. The studies approach NEMS (33,3%), Therapeutic Intervention Scoring System-76 (11,1%), TISS-28 (33,3%), among others. Researches emphasized that NEMS has been a useful, operational and succinct tool.